UNA PROPUESTA DE AULA PARA EL ABORDAJE DE LA REGIÓN DEL ALTO VALLE DE RÍO NEGRO Y NEUQUÉN - Guillermina Muñoz Castillo (Boletín Geográfico)
Within the Postgraduate specialization Educational contents in Geography in National Comahue University, the interest was focused in the study involved North Patagonia region and the spatial transformations derived from global and national economic restructuring in recent times. The present report presents a collection of contents and geographical themes associated with this area, directed to plan a new annual schedule of geographic classroom contents. The idea behind this proposal was the incorporation of the concept of region, considering the High Valley region of Negro and Neuquén rivers as a study case, and the analysis of fruit farming understood as one of the local production processes which clearly show significant changes in its dynamics as a result of the macroeonomic transformations. The objective is to propose contents which allow middle school students to acquire new knowledge about the North Patagonia region, specifically the Alto Valle region of Río Negro and Neuquén, based on the incomplete study of the region as a cross-curricular theme. This presentation offers a new perspective of thinking about new teaching approaches in the classroom in which students’ everyday life would be considered, specially their own representations of their local sphere as a valid tool to build meaningful and socially relevant knowledge. Geography teaching needs to reconsider to meet students’ demands, to provide tools to offer a solution of their problems and practical needs. The construction of a critical and reflexive subject is essential, and Geography, particularly, assumes a formative and assiduous role, because, through its tools, it intends to realise the student’s intervention, turning himself into an active participant of the construction of his reality.